Analysis of Elementary School Teachers’ Readiness for Inclusive Education Programs in Pohuwato - Gui, Marsella Desriyarini (Edumaspul: Jurnal Pendidikan, 2025)
The purpose of this study was to determine the readiness of teachers in Pohuwato to implement an inclusive program in elementary schools, considering the city's cultural, ethnic, and socioeconomic diversity. This research used a qualitative approach known as a case study. Forty-two teachers at elementary schools in Marisa District, Pohuwato Regency, were the subjects of the study. Data were collected through interviews and questionnaires. Teachers also used appropriate learning strategies and models, despite being burdened by administrative tasks. The learning environment provided by the school was quite supportive, but improvements in learning aids were still needed. Parental support played a crucial role in the success of the inclusion program, although only 60% of families actively participated. The results of this study provide important insights for policymakers and relevant parties in improving teacher readiness and support for the inclusion program in Pohuwato. Despite being burdened by administrative tasks, teachers also used appropriate learning strategies and models. Although the school learning environment was very supportive, learning aids were still needed. Although only 60% of families actively participated, parental support played a crucial role in the success of the inclusion program. This research provides policymakers and stakeholders with important insights into how to improve teacher preparedness and support inclusion programs in Pohuwato.